ANABOLIC ANDROGENIC STEROIDS AND ADVERSE EVENTS OF THEIR APPLICATION - Nina Đukanović; Vesko Drašković; Svetlana Višnjić; Zoran Mašić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Anabolic androgenic steroids are synthetic compounds originating from testosterone. Their main effects are the control of development and expression of male secondary sexual characteristics, which are known as androgenic effects, and encourage muscle growth or anabolic effects. Anabolic androgenic steroids are most commonly used illegal substances. Besides these physiological effects, which are achieved using therapeutic doses of these preparations, higher doses than recommended, especially over the longer term, may be associated with the emergence of numerous adverse events. Adverse events may be registered in almost all organs and organ systems, but usually include changes in the reproductive system, skin, liver and cardiovascular system.